Comparing video and poster based education for improving 6-17 months children feeding practices: a cluster randomized trial in rural Benin: Video versus Poster in nutritional education - Bodjrenou, Fifali Sam Ulrich; Amoussa Hounkpatin, Waliou; Mitchodigni, Irène; Salako, Valère; Glèlè Kakaï, Romain; Dadélé, Yzé; Ntandou-Bouzitou, Gervais; Schneider, Lauriina; Mutanen, Marja; Savy, Mathilde; Kennedy, Gina; Hounhouigan, Joseph; et al. (Progress in Nutrition, 2020)
Objective: This study aimed to assess whether short nutrition educational videos were more effectiveto improve child feeding practices compared to posters in a highly food insecure rural area in SouthernBenin. Materials and Methods: A two-arm cluster-randomized trial was implemented in two districts of theMono region, Benin. Over a 6 month period, eight villages received nutrition education sessions using eithershort videos (n=4 villages) or posters and flyers (n=4 villages). Dietary practices were collected among 6-17months children (n=155) before and at the end of the nutrition education program using a qualitative 24 hoursrecall. UNICEF/WHO indicators for dietary diversification and meal frequency assessing were derived foreach child. The videos versus poster effect was assessed by the difference-in-differences (DID) estimator usinggeneralized estimated equations (GEE). Results: Overall, respectively 49% and 72% of children had achievedMinimum Dietary Diversity (MDD) and Minimum Meal Frequency (MMF) at baseline. Results from DIDanalysis showed that videos did not have significant advantage in terms of improving children compared toposters neither for dietary diversity (DID = -0,036; p-value=0,651) nor for meal frequency (DID = -0,048; pvalue=0,574). However, others factors namely children age, mother age and districts, had significant influenceon these feeding practices. Conclusions: The nutrition education program using posters and videos performedthe same in improving complementary feeding practices. The conditions of the utilisation of videos might beimproved and other factors determining children feeding practices taken into account to allow mothers andother participants to benefit from nutrition sessions.